Tuberculosis-related episcleritis: a case report: Poster Presentation - Case Report - Ophthalmologist - RINA WULANDARI; Erdina Hana Jelita (Majalah Oftalmologi Indonesia, 2023)
Introduction : Tuberculosis (TB) is a leading cause of infectious disease in developing and highly endemic countries. Primarily affects the lungs, but also invariably involves ocular tissue. Association of TB and episcleritis is very rarely documented and no such case has been reported in Indonesia. Case Illustration : A 39-year-old female presented with unilateral mild pain and redness of right eye two weeks before admission. It was her fourth episode in one year. Previous steroid and non- steroidal anti- inflammatory drug (NSAID) treatment partially ended her symptoms before reappeared. Rheumatoid disease also TB history of her and her family were denied. There was nodular episcleritis in the inferior part of the right eye. Systemic investigation showed leukocyte and erythrocyte sedimentation rate (ESR) elevation, positive Mantoux test, with normal chest radiograph. Later symptoms and lesion resolved after anti tubercular therapy (ATT). Discussion : Episcleritis is mostly idiopathic, only one third of cases are found to be related with systemic condition. Association of tuberculosis with episcleritis is very rare, only a few cases have been reported worldwide. We encountered a case of tubercular episcleritis by the history of recurrent episode which not responding with regular medication, positive Mantoux test and Indonesia’s TB endemic status. Additionally, improvement after ATT also confirmed the diagnosis. Conclusion : This case suggests that TB can cause episcleritis, especially in TB endemic countries. TB should be considered in facing recurrent episcleritis cases to avoid unnecessary complications.